Pemikiran dan Resistensi Kaum Salafi Terhadap Radikalisme : (Studi Kasus Di Kecamatan Solokuro Paciran Lamongan) - Badrut Tamam, Ahmad; Fatimah, Siti (MADINAH, 2021)
Salafis have two typologies, namely groups that tend to think purely and groups that combine thought and action, this is where there needs to be an analysis because not all salafis are radical. In research using a case study approach, namely at Islamic boarding schools and Umar bin Khatab, the two huts do classify themselves as salafi schools, but in their development the two salafi cottages have different tendencies. The results of this study are that Islamic boarding schools including Islamic boarding schools that carry Jihadi are included in the second typology of thought and action, while Umar bin Khatab Islamic Boarding Schools are more included in the first Salafi typology, namely purifying teachings and returning to their khitah. So from that it was concluded that the Islamic boarding school had seeds and seeds against radicalism, while the Umar bin Khatab Islamic boarding school tried to practice Islam as practiced by the Prophet and the early generations and the Salaf as-shalih. Even so, the two huts in their development tried to survive and were resistant to radicalism, as exemplified by Ali Imron, one of the convicts who had repented, tried to invite the people to return to proper Islamic teachings without becoming a group that rebelled over policies or disapproval, but could not It is avoided that the salafis are still classified as an exclusive group in practicing their religion.